Synchronization of ovulation and subsequent fertility in subestrous buffaloes using a progesterone-based protocol - Ghuman, Sarvpreet Singh (Indian Journal of Dairy Science, 2014)
Ten subestrous buffaloes were administered progesterone release intravaginal insert (Controlled Internal Drug Release, CIDR) for 8 days. On day 7 (day 0: CIDR insertion) and on day 9, all the buffaloes were administered (i.m.) a PGF2α analogue (500µg Cloprostenol sodium) and a GnRH analogue (0.02 mg Buserelin acetate), respectively. Inseminations were carried out on day 10 and thereafter, if required, on day 11. Transrectal ovarian ultrasonography and jugular vein blood sampling was done on various days of protocol. On day 0, ovarian status of the buffaloes revealed the presence of luteal activity (CL diameter: 10.5±1.2 mm, Plasma progesterone: 1.5±0.3 ng/ml). Subsequent to CIDR placement, plasma progesterone concentrations increased (P<0.05) on day 3 (3.0±0.3 ng/ml), and remained above 2.0 ng/ml till day 8. In 80% buffaloes, ovulation occurred between 48-72 h after CIDR removal and during next 24 h in the remaining 20% buffaloes. On day 100, first service conception rate was recorded as 70% (P<0.05). Retrospective analysis suggested that buffaloes failing to conceive had persistently higher luteal activity on day 10 compared to their conceiving counterparts (P<0.05). In conclusion, submission of subestrous buffaloes to a progesterone-based protocol was100% successful for inducing ovulation which was synchronized in 80% buffaloes. Moreover, fertility response was acceptable subsequent to application of this protocol in subestrous buffaloes.